BEBAN KEBIJAKAN DI BUMN DAN REFORMASI BUMN - Muhtar, Muhtar; Achsanta, Aldy Fariz (Jurnal Manajemen, 2023)
Polemics over the management of State Owned Enterprises in various parts of the world, which are full of inefficiency and expropriation by politicians, have prompted major reforms, both in terms of ownership structure and the implementation of good corporate governance. It is hoped that with these reforms, the governance of State Owned Enterprises will become more efficient and transparent. However, the reform of State Owned Enterprises through changes in ownership structure without removing the burden of policy actually makes the privatized State Owned Enterprises perform worse due to being trapped in the soft budget syndrome. Thus, the reform of State Owned Enterprises actually invites a lot of skepticism in several countries. Therefore, this study examines the previous literature that presents empirical and theoretical facts regarding the management of State Owned Enterprises around the world. Based on the previous literature review, State Owned Enterprise reform will be nil if it is not followed by removing the burden of policy. The burden of the policy will be a hindrance for State Owned Enterprises in carrying out efficiency so that State Owned Enterprises will find it difficult to compete with private companies in the market and tend to rely on subsidies or capital assistance from the government to survive. Keywords :State Owned Enterprise, Policy, reformation